Studi Perbandingan Konsep Judicial Pardon berdasarkan KUHP Nasional Indonesia dan Negara Belanda - Hendriwan; Windi Afdal; Ampuan Situmeang (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to understand the concept of judicial pardon in the national Criminal Code, as well as to examine the comparative application of judicial pardon between Indonesia and the Netherlands. This research uses a normative legal research method, applying the statute approach, conceptual approach, comparative approach, and historical approach. Based on the research conducted, the findings are as follows: 1) In the existing legal system, the concept of judicial pardon is not yet recognized or implemented in Indonesia. The mechanism for granting pardon falls under the authority of the executive, namely the President, through the provision of clemency, amnesty, and abolition. Although judicial institutions, such as the Supreme Court, are involved in the consideration process, the final decision remains in the hands of the President. Therefore, it does not reflect the essential characteristic of judicial pardon, which originates from the judiciary itself. 2) The Dutch legal system has implemented the concept of judicial pardon, allowing active involvement of judicial institutions in the pardon-granting process. Although pardons are formally issued by the King, the decisions are based on strong judicial and administrative considerations.